What is Moral Enhancement?. (October 2018) - Rowlands, Mark
Abstract: The idea of moral enhancement has no clear meaning. This is because the idea of being moral has no clear meaning. There are numerous ways in which one might go astray, morally speaking, and each of these ways, in turn, fragments on further analysis. The concept of moral enhancement is as broad, messy, and mottled as the reasons why people behave badly. This mottled character of moral failure calls into question the feasibility of (non-traditional) programmes of moral enhancement.